2001
DOI: 10.1086/320089
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Tracers of the Central 12 Parsecs of the Galactic Center

Abstract: We have used the BIMA array to image the Galactic Center with a 19-pointing mosaic in HCN(1-0), HCO + (1-0), and H 42α emission with 5 km s −1 velocity resolution and 13 ′′ × 4 ′′ angular resolution. The 5 ′ field includes the circumnuclear ring (CND) and parts of the 20 and 50 km s −1 clouds. HCN(1-0) and HCO + trace the CND and nearby giant molecular clouds while the H 42α emission traces the ionized gas in Sgr A West. We find that the CND has a definite outer edge in HCN and HCO + emission at ∼ 45 ′′ radius… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
110
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(117 citation statements)
references
References 38 publications
6
110
1
Order By: Relevance
“…The accelerated molecular gas appears on the front and the back sides of the expanding radio shell. Wright et al (2001) support this scenario from their interferometric HCO + and HCN maps, together with other near blue and redshifted clumps of gas inside of the compressed ridge. A different interpretation was proposed by Liszt & Burton (1995), who detected this feature with very strong emission in CO(3-2) at v ≤ −40 km s −1 , but they considered this feature as an extension of the high-longitude forbidden-velocity part of the CND, as they see a connection between it and the emission arising from the southwestern region of the CND, concluding that Cloud A was not an isolated feature.…”
Section: Hn 13 C Chemistrysupporting
confidence: 55%
See 1 more Smart Citation
“…The accelerated molecular gas appears on the front and the back sides of the expanding radio shell. Wright et al (2001) support this scenario from their interferometric HCO + and HCN maps, together with other near blue and redshifted clumps of gas inside of the compressed ridge. A different interpretation was proposed by Liszt & Burton (1995), who detected this feature with very strong emission in CO(3-2) at v ≤ −40 km s −1 , but they considered this feature as an extension of the high-longitude forbidden-velocity part of the CND, as they see a connection between it and the emission arising from the southwestern region of the CND, concluding that Cloud A was not an isolated feature.…”
Section: Hn 13 C Chemistrysupporting
confidence: 55%
“…These studies have characterized the CND as dense (∼10 5−6 cm −3 ; Marr et al 1993;Marshall et al 1995), clumpy, and very turbulent (with large linewidths). It extends from its inner edge, 1.6 pc from Sgr A * , to > ∼ 2 pc, according to interferometric studies (Wright et al 2001;Christopher et al 2005), and it has an inclination (rotation axis from the line of sight; LOS) of about 60 • −70 • , with the major axis aligned approximately along the Galactic plane (position angle of ∼30 • east of north; Güsten et al 1987;Jackson et al 1993;A&A 526, A54 (2011) Gatley et al (1986) Yusef Telesco et al (1996) Atomic species Liszt et al (1985) (H i, [O Genzel et al (1985) Lugten et al ) Jackson et al (1993) Serabyn et al (1994 Marshall et al 1995). The gas is moving in circular orbits, rotating around the nucleus with a velocity of 110 km s −1 (Liszt et al 1985;Marr et al 1993), but it also presents noncircular motions (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…However, the CND appears not to be a single symmetric structure forming a coherent ring (Marshall et al 1995). It has been suggested that the CND is a warped structure (Guesten et al 1987) or, because of the incompleteness of the ring, formed by A&A 539, A29 (2012) distinct rotating structures (Jackson et al 1993;Wright et al 2001). Most of the observed molecular clumps forming the CND, with diameters of ∼7 , are tidally stable and in virial equilibrium (Christopher et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The mini-spiral of ionized gas consisting of three streamers known as Sgr A West (Lo & Claussen 1983;Ekers et al 1983) is likely feeding the central source. Surrounding Sgr A West, the so-called circumnuclear disk (CND) is a clumpy ringlike structure rotating counterclockwise around the dynamical center (Guesten et al 1987;Wright et al 2001;Christopher et al 2005). The molecular ring extends from its inner sharp edge at a projected distance of 1.6 pc from Sgr A * , out to a smoother edge at ∼2 pc (Christopher et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation